Academic freedom in a plural world: global critical perspectives - Ramanujam, Nandini; Mégret, Frédéric (Central European University Press, 2024)
The notion of academic freedom dates back to the creation of universities and has long been understood to be central to their vocation. This freedom has come under attack by different actors throughout its history. In the current context, rising threats to democracy and human liberties, the corporatization of research, concerns about diversity and increased societal polarization, are putting a considerable pressure on its exercise. However, academic freedom is also a concept that suffers from persistent ambiguities associated with the general notion of freedom as well as debates about the function of universities.